PENERAPAN PENDEKATAN INKUIRI TERBIMBING (GUIDED INQUIRY APPROACH) PADA PEMBELAJARAN FISIKA TERHADAP HASIL BELAJAR DITINJAU DARI MINAT BELAJAR PESERTA DIDIK KELAS X SMA NEGERI 3 JAYAPURA - Sihombing, Rindu (Jurnal Ilmu Pendidikan Indonesia, 2015)
The purposes of this research are : (1) the difference in learning outcomes of students who take the guided inquiry approach to learning and direct instruction, (2) the difference between physics learning outcomes and a high, medium and low level of interest in learning, (3) the interaction application of the learning approach with the level of interest on learning outcomes of students in the subject matter of elasticity. The method used in this study is a quasi experiment with a sample of 60 people, divided into 2 classes (class experimental and control). The results revealed that there were differences in learning outcomes with guided inquiry approach to learning directly with sig learning (0.022)